Aromatic basil (Ocimum x africanum Lour.) tea as a biolarvacide in dengue haemorrhagic fever - Citra Amaniah Anhar; Dewi Inderiati; Diah Lestari; Gina Argiyanti (Poltekkes Kemenkes Bandung, 2026)
Background: Dengue Haemorrhagic Fever is a health problem transmitted by the Aedes aegypti mosquito. Dengue fever control currently still uses chemical larvicides (ABATE) that can pose health and environmental risks, thus requiring natural biolarvicides that are easier to use and effective in controlling mosquito larvae. Objective: To determine the effectiveness of basil leaf tea as a larvicide in killing instar III Aedes aegypti larvae. Methods: This study used a true experimental design with Aedes aegypti instar III larvae as subjects. The treatments consisted of coarsely chopped basil tea and powdered basil tea, both at a 1% concentration. Larvae (20 per replicate) were immersed in 100 mL of the medium for 24 hours, with six replicates. The positive control used ABATE, and the negative control used clean water. Mortality data were analyzed using a one-way ANOVA test. Two treatments of 1% basil tea met the LD50 criteria (mortality≥ 50%) within 24 hours. Results: Coarsely chopped tea produced an average mortality of 60%, while powdered tea produced 55%. The positive control (ABATE) achieved 100% mortality, and the negative control (water) achieved 0%. The One Way ANOVA Post Hoc test showed no statistically significant difference between coarse chopped tea and powdered tea (Sig.= 0.673>0.05). Conclusion: Aromatic basil leaf tea (both coarse and powdered) is effective as a bioinsecticide for controlling DHF, as it can kill and damage the morphology of Aedes aegypti instar III larvae. This tea formulation has the potential to become a safer and more readily available natural larvicide alternative.